PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PADA PT AGUNG AUTOMALL CABANG SIPIN DI PROVINSI JAMBI - Reni Devita (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The purpose of this study is to analyze the influence of leadership style and organizational culture on job satisfaction. Indicators of leadership style are directive leader, supportive leader, participtive leader and achievement oriented leader. Indicators of organizational culture are clan culture, adhocracy culture, hierarchy culture, and market culture. Indicators of job satisfaction are pay satisfaction, promotion satisfaction, supervision satisfaction, coworker satisfaction, and satisfaction with work itself. The primary data was obtained from questionnaires from 60 samples of 144 employees in PT. Agung Automall branch Sipin in Province Jambi. While secondary data were obtained by literatures. Method data analysis used multiple linear regression analysis, using SPSS program version 16.0. The result of the study showed that leadership style, organizational culture, and job satisfaction are good. The result of a mathematical equation is Y = 0,782 + 0,483X1 + 0,326X2 + e. The result showed variable leadership style and organizational culture has a positive impact on job satisfaction. The influence of leadership style and organizational culture on job satisfaction are 40,4 percents and 59, 6 percents job satisfaction is influenced by another variable.Keywords : leadership style, organizational culture, job satisfac